Use of Unregistered Signs in Commercial Transactions: Scope and Limitations of Legal Protection - Repas, Martina (65 pravne znanosti v Mariboru, 2026)
The chapter addresses the legal status of unregistered signs used by undertakings in the course of trade to distinguish their goods and services. Particular emphasis is placed on the well-known mark under Article 6bis of the Paris Convention and its position within the Slovenian legal order, as well as on other unregistered signs that may enable their proprietors to oppose the registration of identical or similar subsequent trademark or to seek the invalidation of an already registered one. The author observes that the scope of protection afforded to unregistered signs under Slovenian law is primarily governed by the Slovenian Competition Act (protection against unfair competition), which essentially affects the possibility of preventing the registration of identical or confusingly similar marks. The chapter focuses particularly on determining which unregistered signs, under what conditions, and on which legal bases can have such capacity.